Diaryltin Dihydrides and Aryltin Trihydrides with Intriguing Stability - Beate G. Steller; Berenike Doler; Roland C. Fischer (Molecules, 2020)
In the last few decades, organotin hydrides have proven their potential as building blocks for a great variety of organometallic compounds. In this context, organotin hydrides with sterically shielding aryl substituents have attracted special interest, as these ligands can kinetically stabilize metastable products. The selective synthesis of aryltin halide compounds Ar*2SnCl2 and Ar*SnI3 featuring the highly sterically encumbered aryl ligand Ar* (iPrAr* = 2,6-(Ph2CH)2-4-iPrC6H2; MeAr* = 2,6-(Ph2CH)2-4-MeC6H2) is presented. These aryltin halides were converted into corresponding aryltin hydrides Ar*2SnH2 and Ar*SnH3, which exhibit a surprisingly high thermal stability and oxygen tolerance.